(untitled) (Pashupati Pragya पशुपति प्रज्ञा, 2026)
Any organization’s success is largely determined by its leadership styles. The way and approach to delivering guidance, implementing program and motivating followers is referred as leadership styles. One of the most important managerial function is leadership and is taken as a crucial aspect for organizational success in these competitive age. The purpose of this study is to investigate the impact of leadership styles on organizational performance. For this study, Nepalese five-star hotels located in Kathmandu Valley are taken and to accomplish the main aim of this study, data are collected from 341 respondents using a structured questionnaire, which are distributed via a convenience sampling method. Descriptive as well as inferential statistics have been administered to analyze and examine data. To test the hypothesis, correlation as well as regression analysis have been implied. The results showed the support to three hypothesis but hypothesis one is rejected with beta coefficient value of autocratic leadership style is -0.168. The findings suggested that there is a positive and significant impact of democratic, transactional as well as transformational leadership on firm’s outcomes in Nepalese five star hotels. Also, the results stated that managers of hotel industry may encourage, develop, and create effective working environment through democratic leadership style.